A biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs and a molding method thereof
By using an ordered porous structure bioscaffold prepared by using insoluble type I collagen, the existing bioscaffolds’ problems of unstable mechanical properties and complex molding processes are solved, achieving efficient ligament repair and a simplified production process.
Patent Information
- Application Number
- CN202411364343.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-29
AI Technical Summary
When repairing ligament damage, existing biological scaffolds have unstable mechanical properties, single load substances, poor load absorption capacity, and complex molding process.
Using insoluble type I collagen as the main raw material, it is designed as a biological scaffold with a cylindrical or waist-shaped structure, with an orderly channel structure evenly arranged along the axial direction, and through specific molding methods, such as shear dispersion, centrifugal concentration and freezing. After drying, a biological scaffold with excellent mechanical properties and liquid absorption rate was prepared.
It improves the mechanical performance and degradation rate of biological brackets, simulates the physiological structure of the front cross ligament, promotes the load of PRP and BMSCS and the deposition of cell components, enhances the integrity and mechanical strength of the biological bracket, and simplifies the molding process.
Smart Images

Figure CN118873745B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of regenerative medicine, and in particular relates to a biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs, and a molding method thereof. Background Art
[0002] Cruciate ligament injuries are mainly repaired by arthroscopic reconstruction surgery. The reconstructed ligament is mainly transplanted by autologous patellar tendon or hamstring tendon, or artificial ligament woven with polymer materials; the main methods of transplantation and fixation of the cruciate ligament are cortical suspension fixation (with titanium plate loop) and interface screw fixation. However, due to the histological characteristics of the anterior cruciate ligament itself, its ability to heal on its own is poor, and if artificial ligament is used, it is expensive and the healing effect is also unsatisfactory.
[0003] Traditional anterior cruciate ligament suturing and reconstruction only involves simple suturing of the injured area or implantation of artificial ligaments. Compared with the "fibrin-platelet clot" of human tissue, it lacks the crucial platelet clot. However, platelet clots contain a large amount of biological factors such as TGF-β, PDGF, bFGF, VEGF, EGF, IGF-1, etc., which can promote a series of biochemical processes such as the differentiation of bone marrow mesenchymal stem cells into fibroblasts and the synthesis of extracellular matrix, thereby improving the repair efficiency. Therefore, a key technology to achieve anterior cruciate ligament repair is whether a temporary ligament similar to the "fibrin-platelet clot" can be constructed at the site of injury to promote the self-repair of the anterior cruciate ligament.
[0004] At present, although there is a regenerative technology that uses bioscaffolds to load related repair factors for repairing ligaments, research in this field still has technical problems such as unstable mechanical properties of bioscaffold raw materials, single loading material, poor load absorption capacity leading to platelet coagulation, and complex molding process. Summary of the invention
[0005] Based on the above technical background, the main purpose of the present invention is to provide a biological scaffold and a molding method thereof for simultaneously loading PRP (platelet-rich plasma) and BMSCs (bone marrow mesenchymal stem cells) for repairing ligament injuries, so as to overcome the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] The first aspect of the present invention is to provide a biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs, wherein the biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs is prepared with insoluble type I collagen as the main raw material;
[0008] The biological stent is a cylindrical structure or a waist-shaped structure, and a plurality of pore structures are evenly arranged in the biological stent along the axial direction of the biological stent, and the pore structures penetrate the biological stent.
[0009] Preferably, the cross-section of the pore structure is circular or polygonal.
[0010] Preferably, the diameter of the pore structure is less than 300 μm.
[0011] The second aspect of the present invention is to provide a method for forming a biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs according to the first aspect of the present invention, the forming method comprising the following steps:
[0012] In step 1,
[0013] Preferably, the acidic solution is selected from one or more of acetic acid, lactic acid and hydrochloric acid; and / or,
[0014] Preferably, the pH value of the acidic solution is 2 to 3.5; and / or,
[0015] Preferably, the solid content of the suspension is 0.3-2%; and / or,
[0016] Preferably, the suspension is shear dispersed at a shear rate of 10000-25000 rpm for 120-240 min. After shear dispersion, the pH is adjusted to 4.5-5.5 at 0-4° C. using an alkaline solution with a pH of 9-11.
[0017] Preferably, the alkaline solution is selected from one or more of aqueous ammonia, sodium bicarbonate solution and sodium hydroxide solution; and / or,
[0018] Preferably, the pH-adjusted suspension is concentrated by centrifugation at 0-8°C and 8000-50000 rpm for 10-30 min, and the concentration after concentration is 5-15%; and / or,
[0019] Preferably, the pre-freezing conditions are: placing the concentrated product on the surface of the refrigerant, descending at a speed of 1 to 7 mm / min for vertical freezing, and the vertical freezing time is 5 to 75 minutes.
[0020] In step 2,
[0021] Preferably, the freeze drying comprises four stages, each stage of the freeze drying process is carried out under a vacuum condition of 0.1 to 0.5 mbar, and the freeze drying procedure is:
[0022] The first stage: cool the pre-frozen bioscaffold from room temperature to 0-4°C for 20-60 minutes, and keep it at 0-4°C for 90-180 minutes;
[0023] The second stage: cooling from 0 to 4°C to -30 to -50°C, the cooling time is 60 to 120 minutes, and keeping at -30 to -50°C for 40 to 120 minutes;
[0024] The third stage: heating from -30 to -50°C to 0 to 4°C, the heating time is 30 to 90 minutes, and keeping at 0 to 4°C for 960 to 1680 minutes;
[0025] The fourth stage: heating from 0-4°C to 15-22°C for 20-60 min, keeping at 15-22°C for 20-90 min, and obtaining a non-cross-linked bioscaffold after freeze-drying.
[0026] More preferably, the non-crosslinked bioscaffold is placed under negative one atmosphere and a temperature of 100-120° C. for 24-75 hours to obtain a physically crosslinked bioscaffold.
[0027] More preferably, EDC and NHS are prepared in a molar ratio of (2-8):1 to obtain a reaction solution, and the non-crosslinked bioscaffold is immersed in the reaction solution and reacted at 2-5°C for 4-12 hours to obtain a chemically crosslinked bioscaffold.
[0028] The beneficial effects of the present invention are:
[0029] (1) The bioscaffold of the present invention uses insoluble type I collagen that can maintain a triple helix structure as the main raw material. Compared with other bioscaffolds prepared using soluble collagen, the bioscaffold of the present invention has better mechanical properties and higher degradation rate.
[0030] (2) Existing bioscaffolds mostly use disordered porous structures, similar to sponge structures, while the bioscaffold described in the present invention uses longitudinal ordered channels that are closer to the anterior cruciate ligament structure. On the one hand, it simulates the original physiological structure of the anterior cruciate ligament tissue, and on the other hand, it can ensure the simultaneous loading of PRP and BMSCs. The ordered porous structure can induce fibroblast differentiation of BMSCs, promote cell migration and arrangement, promote collagen secretion and extracellular matrix deposition, and effectively improve the integrity and mechanical strength of the bioscaffold.
[0031] (3) The bioscaffold of the present invention has an excellent liquid absorption rate and can simultaneously load PRP and BMSCs during use, simulating the original "fibrin-platelet clot" in the tissue and promoting the regeneration of the injured anterior cruciate ligament.
[0032] (4) The bioscaffold molding process described in the present invention can adjust the structure and composition of the obtained product by simply adjusting the centrifugation time and the number of concentrations during centrifugation, thereby obtaining bioscaffolds with different porosities and degradation properties, which can be applied to anterior cruciate ligament injuries of different degrees. The traditional complex molding process is simplified, the production conditions are mild, and the production difficulty is reduced. The performance indicators of the obtained product meet the use requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram showing the structure of the bio-scaffold of the present invention is shown;
[0034] Figure 2 The process flow chart of the bio-scaffold of the present invention is shown;
[0035] Figure 3 The stress-strain curve of the bioscaffold of the present invention is shown. DETAILED DESCRIPTION
[0036] The present invention will be described in detail below, and the characteristics and advantages of the present invention will become clearer and more distinct with the description.
[0037] The first aspect of the present invention is to provide a biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs. The biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs is made of insoluble type I collagen as the main raw material, and the insoluble type I collagen can maintain a triple helix structure.
[0038] The bioscaffold is a cylindrical structure or a waist-shaped structure, wherein the waist-shaped structure is a structure in which the cross-sectional diameters at both ends are larger than the cross-sectional diameter in the middle. A plurality of channel structures are evenly arranged along the axial direction of the bioscaffold, each channel structure is parallel to each other, and the channel structure runs through the bioscaffold.
[0039] Preferably, the cross-section of the pore structure is circular or polygonal.
[0040] Preferably, the diameter of the pore structure is less than 300 μm.
[0041] The bioscaffold is set to a waist-shaped structure, and the cross-sectional diameters at both ends of the bioscaffold are larger, which can increase the contact area with the bone surface, making the fixation of the bioscaffold more stable, and at the same time can load the regeneration factor over a larger area, making the regeneration effect better.
[0042] The collagen content of the biological scaffold is ≥98%, the liquid absorption rate is ≥1000%, and the pore size is ≤300 μm.
[0043] The second aspect of the present invention is to provide a method for forming a biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs according to the first aspect of the present invention, the forming method comprising the following steps: Figure 2 As shown:
[0044] Step 1, dispersing insoluble type I collagen in an acidic solution to obtain a suspension, shearing and dispersing the suspension, adjusting the pH, and then centrifugally concentrating and prefreezing the suspension to obtain a prefrozen bioscaffold;
[0045] Step 2: freeze-drying the pre-frozen bio-scaffold to obtain the bio-scaffold.
[0046] The above steps are described in detail below.
[0047] In step 1, the acidic solution is selected from one or more of acetic acid, lactic acid, and hydrochloric acid. Preferably, the acidic solution is acetic acid, lactic acid, or hydrochloric acid.
[0048] The pH value of the acidic solution is 2-3.5, preferably, the pH value of the acidic solution is 2.5-3.2.
[0049] The solid content of the suspension is 0.3-2%, preferably, the solid content of the suspension is 0.5-1.5%.
[0050] The suspension is shear dispersed at a shear rate of 10000-25000 rpm for 120-240 minutes. After shear dispersion, an alkaline solution with a pH of 9-11 is used to adjust the pH to 4.5-5.5 at 0-4°C.
[0051] Preferably, the suspension is shear dispersed at a shear rate of 12000-20000 rpm for 180 min. After shear dispersion, the pH is adjusted to 4.6-4.8 at 0° C. using an alkaline solution having a pH of 10.
[0052] The alkaline solution is selected from one or more of aqueous ammonia, sodium bicarbonate solution and sodium hydroxide solution.
[0053] Preferably, the alkaline solution is aqueous ammonia, sodium bicarbonate solution or sodium hydroxide solution.
[0054] The pH-adjusted suspension is concentrated by centrifugation at 0-8°C and 8000-50000 rpm for 10-30 min. The concentration after concentration is 5-15%.
[0055] Preferably, the suspension after pH adjustment is concentrated by centrifugation at 4-6° C. and 10,000-20,000 rpm for 10-20 min, and the concentration after concentration is 10%.
[0056] The pre-freezing conditions are as follows: placing the concentrated product on the surface of the refrigerant, descending at a speed of 1 to 7 mm / min for vertical freezing, and the vertical freezing time is 5 to 75 minutes.
[0057] Preferably, the pre-freezing conditions are: placing the concentrated product on the surface of liquid nitrogen, and descending at a speed of 1 to 5 mm / min for vertical freezing, and the vertical freezing time is 10 to 60 minutes.
[0058] The pre-freezing stage is crucial for the formation of vertical channels. In the concentration step, a detachable polytetrafluoroethylene or metal centrifuge tube is used for the operation. The centrifuge tube is lowered to the surface of the refrigerant (liquid nitrogen or other refrigerants can be used, preferably liquid nitrogen because liquid nitrogen can provide more supercooling), and then lowered at a speed of 1-5 mm / min for vertical freezing. The tube stays for 10-60 minutes. After the pre-freezing is completed, the centrifuge tube is opened and the sample is taken out for the subsequent freeze-drying process.
[0059] In step 2, the freeze drying includes four stages, and each stage of the freeze drying process is carried out under a vacuum condition of 0.1 to 0.5 mbar. The freeze drying procedure is:
[0060] The first stage: cool the pre-frozen bioscaffold from room temperature to 0-4°C for 20-60 minutes, and keep it at 0-4°C for 90-180 minutes;
[0061] The second stage: cooling from 0 to 4°C to -30 to -50°C, the cooling time is 60 to 120 minutes, and keeping at -30 to -50°C for 40 to 120 minutes;
[0062] The third stage: heating from -30 to -50°C to 0 to 4°C, the heating time is 30 to 90 minutes, and keeping at 0 to 4°C for 960 to 1680 minutes;
[0063] The fourth stage: heating from 0-4°C to 15-22°C for 20-60 minutes, and keeping at 15-22°C for 20-90 minutes. After freeze drying, the non-crosslinked bioscaffold is obtained.
[0064] Preferably, the freeze drying comprises four stages, each stage of the freeze drying process is carried out under a vacuum condition of 0.3 mbar, and the freeze drying procedure is:
[0065] The first stage: cool the pre-frozen bioscaffold from room temperature to 0°C for 30 to 60 minutes, and keep it at 0°C for 120 to 180 minutes;
[0066] The second stage: cooling from 0℃ to -40℃, the cooling time is 80-120min, and keeping at -40℃ for 60-120min;
[0067] The third stage: heating from -40℃ to 0℃, the heating time is 40~90min, and keeping at 0℃ for 1080~1680min;
[0068] The fourth stage: heating from 0°C to 20°C for 30 to 60 minutes, and keeping at 20°C for 30 to 60 minutes. After freeze drying, the non-crosslinked bioscaffold is obtained.
[0069] According to a preferred embodiment of the present invention, a non-crosslinked biological scaffold is placed under negative one atmosphere and a temperature of 100-120° C. for 24-75 hours to obtain a physically crosslinked biological scaffold.
[0070] More preferably, the non-crosslinked bioscaffold is placed under a temperature of 105° C. and a pressure of -1 atmosphere for 72 hours to obtain a physically crosslinked bioscaffold.
[0071] According to a preferred embodiment of the present invention, EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide) and NHS (N-hydroxysulfosuccinimide) are prepared in a molar ratio of (2-8):1 to obtain a reaction solution, and a non-cross-linked bioscaffold is immersed in the reaction solution and reacted at 2-5°C for 4-12 hours to obtain a chemically cross-linked bioscaffold.
[0072] More preferably, EDC and NHS are prepared in a molar ratio of 4:1 to obtain a reaction solution, and the non-crosslinked bioscaffold is immersed in the reaction solution and reacted at 4° C. for 8 h to obtain a chemically crosslinked bioscaffold.
[0073] Example
[0074] The present invention is further described below by specific examples, which are limited to illustrating the present invention but not to limiting the scope of the present invention. The raw materials used in the examples of the present invention were all purchased.
[0075] Example 1
[0076] The biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs is made of insoluble type I collagen as the main raw material. The biological scaffold is a cylindrical structure with an overall size of 44 mm (height) × 22 mm (diameter). The pore structure is evenly arranged along the axial direction of the biological scaffold in the biological scaffold. The cross-section of the pore structure is circular, and the diameter of the pore structure is ≤300. μ m, such as Figure 1 shown.
[0077] Example 2
[0078] Take 5 g of insoluble type I collagen and disperse it in 1000 mL of glacial acetic acid solution with a pH of 3.2. At this time, the solid content of the suspension is 0.5%. Then, the suspension is sheared and dispersed at a speed of 12,000 rpm for 180 min at 0°C using a high-speed shearing machine. After dispersion, adjust the pH of the dispersion to 4.7 at 0°C using dilute ammonia water with a pH of 10. Concentrate the above suspension using a low-temperature high-speed centrifuge at a speed of 12,000 rpm for 10 min at 6°C. Place the centrifuge tube used for concentration on the surface of liquid nitrogen, then descend at a speed of 2 mm / min for vertical freezing (pre-freezing), stay for 15 minutes, open the centrifuge tube after pre-freezing, take out the sample and freeze-dry it according to the following procedure:
[0079] (1) The room temperature was cooled to 0°C and kept at a constant temperature. The cooling process took 30 min and the constant temperature process took 120 min.
[0080] (2) Cooling from 0°C to -40°C and maintaining the temperature. The cooling process takes 80 min and the temperature maintenance process takes 60 min.
[0081] (3) Heating from -40°C to 0°C and maintaining the temperature, the heating process takes 40 min and the temperature maintenance process takes 1080 min;
[0082] (4) The temperature is raised from 0°C to 20°C for 30 min and kept at a constant temperature for 30 min. The vacuum degree in each of the above steps is maintained at 0.3 mbar. After the freeze-drying process is completed, a non-cross-linked bioscaffold is obtained.
[0083] Example 3
[0084] Take 7.5 g of insoluble type I collagen and disperse it in 1000 mL of lactic acid solution with pH=3.2. At this time, the solid content of the suspension is 0.75%. Then, the suspension is sheared and dispersed at 12000 rpm for 180 min at 0°C using a high-speed shearing machine. After dispersion, adjust the pH of the dispersion to 4.8 at 0°C using a sodium bicarbonate solution with pH=10. Concentrate the above suspension using a low-temperature high-speed centrifuge at 10000 rpm for 15 min at 4°C. Place the centrifuge tube used for concentration on the surface of liquid nitrogen, then descend at a speed of 3 mm / min for vertical freezing (pre-freezing), stay for 10 min, open the centrifuge tube after pre-freezing, take out the sample and freeze-dry it according to the following procedure:
[0085] (1) The room temperature was cooled to 0°C and kept at a constant temperature. The cooling process took 40 min and the constant temperature process took 150 min.
[0086] (2) Cooling from 0°C to -40°C and maintaining the temperature, the cooling process takes 80 min, and the temperature maintenance process takes 80 min;
[0087] (3) Heating from -40°C to 0°C and maintaining the temperature, the heating process takes 60 min and the temperature maintenance process takes 1320 min;
[0088] (4) The temperature was raised from 0°C to 20°C for 40 min and kept at a constant temperature for 40 min. The vacuum degree in each of the above steps was maintained at 0.3 mbar. After the freeze-drying process was completed, a non-cross-linked bioscaffold was obtained.
[0089] Example 4
[0090] Take 15g of insoluble type I collagen and disperse it in 1000mL of hydrochloric acid solution with pH=2.5. At this time, the solid content of the suspension is 1.5%. Then, the suspension is sheared and dispersed at 20,000 rpm for 180min at 0°C using a high-speed shearing machine. After dispersion, adjust the pH of the dispersion to 4.6 at 0°C using a sodium hydroxide solution with pH=10. Concentrate the above suspension using a low-temperature high-speed centrifuge at 20,000 rpm for 20 min at 4°C. Place the centrifuge tube used for concentration on the surface of liquid nitrogen, then descend at a speed of 1 mm / min for vertical freezing (pre-freezing), stay for 10 minutes, open the centrifuge tube after pre-freezing, take out the sample and freeze-dry it according to the following procedure:
[0091] (1) The room temperature was cooled to 0°C and kept at a constant temperature. The cooling process took 60 min and the constant temperature process took 180 min.
[0092] (2) Cooling from 0°C to -40°C and maintaining the temperature. The cooling process takes 120 min, and the temperature maintenance process takes 120 min.
[0093] (3) Heating from -40°C to 0°C and maintaining the temperature, the heating process takes 90 min and the temperature maintenance process takes 1680 min;
[0094] (4) The temperature is raised from 0°C to 20°C for 60 min and maintained at a constant temperature for 60 min. The vacuum degree in each of the above steps is maintained at 0.2 mbar. After the freeze-drying process is completed, a non-cross-linked bioscaffold is obtained.
[0095] Example 5
[0096] Take 5 g of insoluble type I collagen and disperse it in 1000 mL of glacial acetic acid solution with a pH of 3.2. At this time, the solid content of the suspension is 0.5%. Then, the suspension is sheared and dispersed at a speed of 12,000 rpm for 180 min at 0°C using a high-speed shearing machine. After dispersion, adjust the pH of the dispersion to 4.7 at 0°C using dilute ammonia water with a pH of 10. Concentrate the above suspension using a low-temperature high-speed centrifuge at a speed of 12,000 rpm for 10 min at 6°C. Place the centrifuge tube used for concentration on the surface of liquid nitrogen, then descend at a speed of 5 mm / min for vertical freezing (pre-freezing), stay for 60 minutes, open the centrifuge tube after pre-freezing, take out the sample and freeze-dry it according to the following procedure:
[0097] (1) The room temperature was cooled to 0°C and kept at a constant temperature. The cooling process took 30 min and the constant temperature process took 120 min.
[0098] (2) Cooling from 0°C to -40°C and maintaining the temperature. The cooling process takes 80 min and the temperature maintenance process takes 60 min.
[0099] (3) Heating from -40°C to 0°C and maintaining the temperature, the heating process takes 40 min and the temperature maintenance process takes 1080 min;
[0100] (4) The temperature was raised from 0°C to 20°C for 30 min and maintained at a constant temperature for 30 min. The vacuum degree was maintained at 0.3 mbar in each of the above steps.
[0101] The freeze-dried product was placed in a vacuum oven, the vacuum degree was adjusted to minus one atmosphere, the temperature was 105°C, and the drying time was 72 h. After the reaction was completed, a physically cross-linked bioscaffold was obtained.
[0102] Example 6
[0103] Take 5 g of insoluble type I collagen and disperse it in 1000 mL of glacial acetic acid solution with a pH of 3.2. At this time, the solid content of the suspension is 0.5%. Then, the suspension is sheared and dispersed at a speed of 12,000 rpm for 180 min at 0°C using a high-speed shearing machine. After dispersion, adjust the pH of the dispersion to 4.7 at 0°C using dilute ammonia water with a pH of 10. Concentrate the above suspension using a low-temperature high-speed centrifuge at a speed of 12,000 rpm for 10 min at 6°C. Place the centrifuge tube used for concentration on the surface of liquid nitrogen, then descend at a speed of 4 mm / min for vertical freezing (pre-freezing), stay for 30 minutes, open the centrifuge tube after pre-freezing, take out the sample and freeze-dry it according to the following procedure:
[0104] (1) The room temperature was cooled to 0°C and kept at a constant temperature. The cooling process took 30 min and the constant temperature process took 120 min.
[0105] (2) Cooling from 0°C to -40°C and maintaining the temperature. The cooling process takes 80 min and the temperature maintenance process takes 60 min.
[0106] (3) Heating from -40°C to 0°C and maintaining the temperature, the heating process takes 40 min and the temperature maintenance process takes 1080 min;
[0107] (4) The temperature was raised from 0°C to 20°C for 30 min and maintained at a constant temperature for 30 min. The vacuum degree was maintained at 0.3 mbar in each of the above steps.
[0108] The reaction solution is prepared with EDC and NHS in a molar ratio of 4:1, and the freeze-dried product is immersed in the solution and reacted at 4°C for 8 h to obtain a chemically cross-linked bioscaffold.
[0109] Experimental example
[0110] Experimental Example 1 Mechanical Properties Test
[0111] The mechanical properties of the collagen scaffold were tested by testing the tensile strength. The specific test steps were as follows: the scaffold sample prepared in Example 2 was cut into a strip of 50 × 10 mm in size, and its thickness was measured using an electronic universal testing machine. The two ends of the sample were fixed with the clamps of the electronic universal testing machine, and the tensile strength of the scaffold material was tested at a tensile rate of 1 mm / min. Three samples of each scaffold material were averaged and the experiment was repeated three times. The calculation formula was: Ts = F / S.
[0112] Where Ts is the tensile strength; F is the maximum tensile force the material is subjected to when it breaks, N; S is the area of the fractured section of the material, mm 2 The stress-strain curve is as follows: Figure 3 shown.
[0113] After testing, according to Figure 3 , and the calculation formula, the tensile modulus of the bioscaffold prepared in Example 2 is 15.200 MPa, and the elongation at break is 51.7%, indicating that the bioscaffold of the present invention has excellent mechanical properties.
[0114] Experimental Example 2 Degradation Rate Test
[0115] The test steps are as follows: Use PBS buffer to prepare a type I collagenase solution with a concentration of 30 U / mL as a degradation solution. Weigh about 50 mg of the bioscaffold material sample prepared in Example 2 and place it in a test tube. Add 20 mL of the prepared degradation solution to completely immerse the material sample. Seal the test tube and place it in a constant temperature water bath at 37°C. After 48 hours, freeze-dry the remaining undegraded bioscaffold material and weigh it. Repeat the experiment three times, and calculate the degradation rate according to the following formula:
[0116] D(%) = (W1 − W2) / W1× 100
[0117] Where D is the degradation rate, W1 is the weight before degradation, and W2 is the weight after degradation.
[0118] The test results are shown in Table 1:
[0119] Table 1
[0120]
[0121] As can be seen from Table 1, the degradation rate is 50%-70% when the degradation time is 12 h, 60%-75% when the degradation time is 24 h, and 90%-100% when the degradation time is 36 h, indicating that the bioscaffold material of the present invention can be completely degraded and has a high degradation rate.
[0122] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
Claims
1. A method for forming a bioscaffold for repairing ligament damage and simultaneously loading PRP and BMSCs, characterized in that: The biological scaffold for repairing ligament damage and simultaneously loading PRP and BMSCs is prepared with insoluble type I collagen as the main raw material; The bio-scaffold is a cylindrical structure or a waist-shaped structure, and a plurality of pore structures are evenly arranged in the bio-scaffold along the axial direction of the bio-scaffold, and the pore structures penetrate the bio-scaffold; The molding method comprises the following steps: Step 1, dispersing insoluble type I collagen in an acidic solution to obtain a suspension, shearing and dispersing the suspension, adjusting the pH, and then centrifugally concentrating and prefreezing the suspension to obtain a prefrozen bioscaffold; Step 2, freeze-drying the pre-frozen bio-scaffold to obtain the bio-scaffold; In step 1, the suspension is sheared and dispersed at a shear rate of 10000 to 25000 rpm for 120 to 240 minutes. After shearing and dispersion, an alkaline solution with a pH of 9 to 11 is used to adjust the pH to 4.5 to 5.5 at 0 to 4° C.; The alkaline solution is selected from one or more of aqueous ammonia, sodium bicarbonate solution and sodium hydroxide solution; The pH-adjusted suspension is concentrated by centrifugation at 0-8°C and 8000-50000 rpm for 10-30 min, and the concentration after concentration is 5-15%; The pre-freezing conditions are as follows: placing the concentrated product on the surface of the refrigerant and dropping it at a speed of 1 to 7 mm / min for vertical freezing, and the vertical freezing time is 5 to 75 minutes; In step 2, the freeze drying includes four stages, and each stage of the freeze drying process is carried out under a vacuum condition of 0.1 to 0.5 mbar. The freeze drying procedure is: The first stage: cool the pre-frozen bioscaffold from room temperature to 0-4°C for 20-60 minutes, and keep it at 0-4°C for 90-180 minutes; The second stage: cooling from 0 to 4°C to -30 to -50°C, the cooling time is 60 to 120 minutes, and keeping at -30 to -50°C for 40 to 120 minutes; The third stage: heating from -30 to -50°C to 0 to 4°C, the heating time is 30 to 90 minutes, and keeping at 0 to 4°C for 960 to 1680 minutes; The fourth stage: heating from 0-4°C to 15-22°C for 20-60 min, keeping at 15-22°C for 20-90 min, and obtaining a non-cross-linked bioscaffold after freeze-drying.
2. The molding method according to claim 1, characterized in that: The cross section of the pore structure is circular or polygonal.
3. The molding method according to claim 1, characterized in that: The diameter of the pore structure is less than 300 μm.
4. The molding method according to claim 1, characterized in that: In step 1, The acidic solution is selected from one or more of acetic acid, lactic acid and hydrochloric acid; and / or, The pH value of the acidic solution is 2 to 3.5; and / or, The solid content of the suspension is 0.3-2%.
5. The molding method according to claim 1, characterized in that: In step 2, The non-crosslinked biological scaffold is placed under the conditions of negative one atmospheric pressure and a temperature of 100-120° C. for 24-75 hours to obtain a physically crosslinked biological scaffold.
6. The molding method according to claim 1, characterized in that: In step 2, EDC and NHS are prepared in a molar ratio of (2-8):1 to obtain a reaction solution, and a non-cross-linked bioscaffold is immersed in the reaction solution and reacted at 2-5°C for 4-12 hours to obtain a chemically cross-linked bioscaffold.
Citation Information
Patent Citations
Preparation and use of I -type collagen artificial tendon, ligaments
CN101332134A
I-type medical collagen material keeping original specific triple helix structure of collagen, product and application thereof
CN101569765A